A Novel Dynamin 2 Mutation Causing Dominant Intermediate Charcot-Marie-Tooth Neuropathy: Case Report - Carmela V. San Luis MD; Coreen Schwartzlow MD; Kenkichi Nozaki MD, PhD; Eroboghene E. Ubogu MD (SAGE Publishing, 2022)
Dynamin 2 mutations are associated with Charcot-Marie-Tooth neuropathy. We report two siblings with a novel missense heterozygous point mutation (c.1609 G>A) in the highly conserved pleckstrin homology domain in exon 15 of Dynamin 2 presenting with progressive length-dependent sensorimotor polyneuropathy with mixed demyelinating and axonal features on electrodiagnostic studies. The previously unrecognized missense point mutation, which was inherited from their symptomatic but previously undiagnosed mother, was determined to be likely pathogenic based on a non-conservative amino acid substitution (p.Gly537Ser) that is predicted to damage secondary protein structure or function. This report emphasizes the importance of recognizing inherited neuropathies in clinical practice and evaluating suspected pathogenic gene variants initially classified to be of undetermined clinical significance in family cohorts. These cases add to the spectrum of pathogenic Dynamin 2 mutations associated with dominant-intermediate Charcot-Marie-Tooth neuropathy.